Computer and Mobile Forensic Approach to Acquire Audit Evidence at the Audit Board of the Republic of Indonesia - Veronika Veronika; Hendratna Mutaqin (Budapest International Research and Critics University, 2022)
Computer and mobile forensic is a new technique for most auditor in the Audit Board of the Republic of Indonesia (BPK). They can use this technique not only for investigative audit but also for state finance and performance audit. Investigative Audit Unit in BPK has already implemented computer and mobile forensic technique to support their assignment although need to improve in several areas. On the other hand, only a few of auditors outside Investigative Audit Unit know and implement this technique. The current issues in implementing this technique is BPK still do not make a special guidance for computer and mobile forensic. The recommendations for BPK regarding the result of the study project is organize a computer and mobile forensic training for all auditors and make a guidance of computer and mobile forensic techniques for auditor.